The Impact of Message Source on the Effectiveness of Communications About Climate Change. Issue 4 (August 2019) - Bolsen, Toby; Palm, Risa; Kingsland, Justin T.
We conducted a survey experiment in which we presented 1, 850 respondents with one of two versions of an appeal emphasizing either the threats to the environment or threats to national security of the United States as a result of climate change. The messages were attributed to one of four sources: Republican Party leaders, Democratic Party leaders, military officials, or climate scientists. The results reveal that messages attributed to military leaders, or to Republican Party leaders, can enhance the impact of the appeal. This finding underscores the importance that the source of any communication can have on its overall effectiveness.